Study of Reasons for Breastfeeding Cessation in Basra City During The First Six Months Following Childbirth - Taqi, Noor Hasan Mohamed; Hadeel H. Haider; Nadia Kaleel Abduljaleel (Indonesian Journal on Health Science and Medicine, 2025)
Breastfeeding is universally recognized as the optimal source of infant nutrition, providing essential immunological, psychological, and developmental benefits for both mother and child. Specific Background: Despite the World Health Organization’s recommendation for exclusive breastfeeding during the first six months postpartum, global and regional adherence remains low, with many women discontinuing early. Knowledge Gap: Limited studies in Basra have systematically investigated the underlying reasons for breastfeeding cessation within the critical first six months. Aims: This study aimed to identify the main causes of breastfeeding cessation among mothers in Basra and assess associations with socio-demographic and obstetric factors. Results: A total of 158 mothers were included. Most participants were 26–35 years old (56.4%), urban residents (76.6%), and of moderate financial level (75.3%). Only 31% practiced breastfeeding, while 48.1% relied on bottle feeding. The majority (68.4%) breastfed for 1–6 months, and only 16.5% continued beyond one year. Early cessation was not significantly associated with demographic or obstetric factors except parity, as multiparous mothers were more likely to continue breastfeeding. The leading reason for cessation was the perception of insufficient milk supply (36.7%), followed by time constraints (14.6%) and family influence (14%). This study highlights false perceptions of inadequate milk supply as a key, modifiable determinant of breastfeeding cessation in Basra, emphasizing the role of maternal experience and parity. Strengthening antenatal and postnatal counseling, enhancing family support, and improving primary health care interventions are critical for promoting longer breastfeeding duration and overcoming preventable barriers. Highlights Only 31% of mothers in Basra practiced breastfeeding, while 48.1% relied on bottle feeding. The main reason for early breastfeeding cessation was the perception of insufficient milk supply (36.7%). Multiparous mothers were significantly more likely to continue breastfeeding compared to primiparous mothers.